Influence of Deposition Temperature of GDC Interlayer Deposited by RF Magnetron Sputtering on Anode‐Supported SOFC. Issue 2 (13th February 2014) - Wu, W.; Wang, X.; Liu, Z.; Zhao, Z.; Ou, D.; Tu, B.; Cheng, M.
Abstract Gadolinia‐doped ceria (GDC) film, as a barrier layer to prevent chemical reaction between yttria‐stabilized zirconia (YSZ) electrolyte and Ba0.5Sr0.5Co0.8Fe0.2O3–δ (BSCF)–GDC cathode, is deposited by radio frequency (RF) magnetron sputtering on YSZ electrolyte, and the influence of deposition temperature on Ni–YSZ/YSZ/GDC/BSCF–GDC single cell performance is investigated. The SEM results show that the GDC film deposited at 30 °C exhibits a porous structure, whereas the GDC film deposited at 400 °C has a dense structure. The single cells show excellent performance when the deposition temperature is above 250 °C, whereas the single cells show poor performance when the deposition temperature is below 200 °C. The large difference in cell performance occurs from their large difference in polarization resistance. The porous structure of GDC interlayer, which cannot well prevent the reaction between BSCF and YSZ, is responsible for the poor performance of the cells with GDC interlayer deposited at a temperature below 200 °C.